2015
DOI: 10.1002/2015jc010892
|View full text |Cite
|
Sign up to set email alerts
|

Internal lee wave closures: Parameter sensitivity and comparison to observations

Abstract: This paper examines two internal lee wave closures that have been used together with ocean models to predict the time‐averaged global energy conversion rate into lee waves and dissipation rate associated with lee waves and topographic blocking: the Garner (2005) scheme and the Bell (1975) theory. The closure predictions in two Southern Ocean regions where geostrophic flows dominate over tides are examined and compared to microstructure profiler observations of the turbulent kinetic energy dissipation rate, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…In the bottom kilometer, the velocity field is particularly enhanced, indicating large-amplitude lee waves, which break and dissipate some of their energy right after their generation. Patches of very high velocity seen behind steep topographic features are associated with low-level, nonradiating, nonlinear motions such as topographically blocked flows (e.g., Trossman et al 2015;Dossmann et al 2016;Klymak 2018) and hydraulic jumps (e.g., Baines 1995). Overall, the results are consistent with previous numerical simulations (e.g., Nikurashin and Ferrari 2010b;Nikurashin et al 2014) and show that the flow response is a superposition of different motions arising from the interaction of a uniform mean flow with realistic, multiscale rough topography.…”
Section: A Reference Experiment: Uniformly Rough Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…In the bottom kilometer, the velocity field is particularly enhanced, indicating large-amplitude lee waves, which break and dissipate some of their energy right after their generation. Patches of very high velocity seen behind steep topographic features are associated with low-level, nonradiating, nonlinear motions such as topographically blocked flows (e.g., Trossman et al 2015;Dossmann et al 2016;Klymak 2018) and hydraulic jumps (e.g., Baines 1995). Overall, the results are consistent with previous numerical simulations (e.g., Nikurashin and Ferrari 2010b;Nikurashin et al 2014) and show that the flow response is a superposition of different motions arising from the interaction of a uniform mean flow with realistic, multiscale rough topography.…”
Section: A Reference Experiment: Uniformly Rough Topographymentioning
confidence: 99%
“…A possible explanation is that part of the lee wave energy can be absorbed by the mean flow through the wave-mean flow interaction, when the mean flow is characterized by a large near-bottom shear (Waterman et al 2014). Finally, Trossman et al (2015) suggested that anisotropy in abyssal hill topography and the relative orientation of the bottom flow with respect to this anisotropy, not taken into account in theoretical estimates, may also contribute to local overestimation of the wave energy radiation.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative parameterization for quasi‐steady oceanic lee waves, based on Garner 's [] scheme for topographic interaction in the atmosphere, was introduced by Trossman et al . []. Their scheme includes nonlinear processes such as topographic blocking, which produces higher estimates of turbulent dissipation in the lower 1000 m of the ocean than schemes based on Bell [].…”
Section: Introductionmentioning
confidence: 99%
“…Trossman et al . [] make the case that better observations, particularly close to topography, are needed to validate lee wave closure schemes.…”
Section: Introductionmentioning
confidence: 99%
“…In the Trossman et al (2013Trossman et al ( , 2016 studies, the vertical structure and amplitudes of eddy kinetic energy are altered in the presence of the parameterized lee wave drag, but the internal lee waves themselves are not generated in the global simulations, which cannot be run at high enough horizontal resolution to resolve lee waves. Finally, Trossman et al (2015) employed the roughness maps to compare the internal lee wave conversions predicted by the Bell (1975) theory and the Garner (2005) scheme with dissipation rates measured by microstructure profilers in two different Southern Ocean field campaigns. In summary, the Goff and Arbic (2010) and Goff (2010) synthetic roughness fields have been used in two different ways in previous studies-the roughness impacts either a wave drag parameterization that is subsequently inserted into a model of low-frequency flows, or is used as an input for a linear analysis of energy conversion into internal waves (from either tidal or low-frequency flows).…”
Section: Introductionmentioning
confidence: 99%